(untitled) (Web of Teachers: Inderscience Research, 2024)
The article presents the material of the results of a pedagogical study devoted to improving the development of speed and strength abilities of young athletes aged 11-12 years of the second year of study in a specialized sports school. The material of the article contains special tools and methods implemented in special complexes and the results obtained at the end of the study.